(untitled) (Proceedings of the World Conference on Waste Management, 2021)
As part of its new sustainability goal “Zero Waste”, General Motors aims to divert 90% of its total waste generation from landfills and incineration with or without energy recovery by 2025. To achieve this goal, it is necessary to determine the correct method to track the percentage of waste diverted over time, since it will be the key performance indicator (KPI) of the program. The most accepted method to calculate this KPI is by dividing the total amount of waste diverted from landfills and/or incinerators by the total amount of waste generated in a specific time period. This methodology presents a simple snapshot of the current performance and does not fully address the long-term performance. The new proposal aims to track performance over time using similar approach as defined in the revised edition of the Greenhouse Gas Protocol. The new methodology uses a baseline to track performance and determines the diversion rate by comparing the total nondiverted material against the baseline. This method has shown accurate percentage of diversion rate and improved the company’s data management since past data was used to calculate the baseline.